Piperlongumine Acts as an Immunosuppressant by Exerting Prooxidative Effects in Human T Cells Resulting in Diminished TH17 but Enhanced Treg Differentiation - Liang, Jie; Ziegler, Jacqueline D.; Jahraus, Beate; Orlik, Christian; Blatnik, Renata; Blank, Norbert; Niesler, Beate; Wabnitz, Guido; Ruppert, Thomas; Hübner, Katrin; Balta, Emre; Samstag, Yvonne (Frontiers in Immunology, 2020)
Piperlongumine (PL), a natural small molecule derived from the Piper longum Linn plant, has received growing interest as a prooxidative drug with promising anticancer properties. Yet, the influence of PL on primary human T cells remained elusive. Knowledge of this is of crucial importance, however, since T cells in particular play a critical role in tumor control. Therefore, we investigated the effects of PL on the survival and function of primary human peripheral blood T cells (PBTs). While PL was not cytotoxic to PBTs, it interfered with several stages of T cell activation as it inhibited T cell/APC immune synapse formation, costimulation-induced upregulation of CD69 and CD25, T cell proliferation and the secretion of proinflammatory cytokines. PL-induced immune suppression was prevented in the presence of thiol-containing antioxidants. In line with this finding, PL increased the levels of intracellular reactive oxygen species and decreased glutathione in PBTs. Diminished intracellular glutathione was accompanied by a decrease in S-glutathionylation on actin suggesting a global alteration of the antioxidant response. Gene expression analysis demonstrated that TH17-related genes were predominantly inhibited by PL. Consistently, the polarization of primary human naïve CD4+ T cells into TH17 subsets was significantly diminished while differentiation into Treg cells was substantially increased upon PL treatment. This opposed consequence for TH17 and Treg cells was again abolished by thiol-containing antioxidants. Taken together, PL may act as a promising agent for therapeutic immunosuppression by exerting prooxidative effects in human T cells resulting in an upregulation of Treg cells and downregulation of TH17 cells.